Genome-Wide Association Meta-Analysis for Acute Rejection of Kidney Transplants. (July 2018) - Israni, Ajay K.; Jacobson, Pamala A.; Guan, Weihua; Dorr, Casey R.; van Setten, Jessica; de Borst, Martin H.; Stapleton, Caragh P.; Phelan, Paul J.; Conlon, Peter J.; Birdwell, Kelly A.; Reindl-Schwaighofer, Roman; Heinzel, Andreas; et al.
Abstract : International Genetics & Translational Research in Transplantation Network (iGeneTRAiN). Background: Evidence is limited regarding acute rejection (AR) beyond human leukocyte antigens and studies investigating genetic background of AR are limited in size. This study combined genome-wide association studies (GWAS) following kidney transplantation to increase power and further understand mechanisms of AR. The cohorts in this meta-analysis are from the International Genetics and Translational Research in Transplantation Network (iGeneTRAiN). Methods: We performed a GWAS meta-analysis of AR anytime post-transplant in Caucasian recipients and donors after kidney transplantation using the "Tx Array" containing ~782, 000 single-nucleotide polymorphisms (SNPs). AR was defined by treating physician. Genotype imputation was based on the 1000 Genomes project and Genomes of The Netherlands reference datasets. The analysis was adjusted for age, sex, living/deceased donors, and population stratification using principal components. We ran a fixed effect, inverse variance, meta-analysis to combine results from 7 cohorts. SNPs that were deemed to reach GWAS significance had p < 1x10-6, population frequency between 0.01 and 0.99 and R2 for imputation quality > 0.8. Results: The meta-analysis of 7 GWAS cohorts in iGeneTRAiN included 5, 291 kidney transplant recipients with 1265 (24%) AR events (Table 1). Thirty recipient SNPs reached GWAS significance for their association with AR. The recipient SNP with strongest AR association was rs294768 (p = 1.24 x10-8) located 7.9 kb 5' of UGT2B10. 14 of the 30 top recipient SNPs were located in or near UGT2B10, including rs2942857, which is an mRNA splice acceptor (p = 2.59x10-7). 3 significant recipient SNPs were located in or near each of UNC5D, CA10, and NLGN1. 39 donor SNPs reached GWAS significance for their association with AR. The top donor SNPs were: rs137878631, 33kb 3' of DMP1 (p = 2.61x10-8); rs78140122, intron of MARCH1 (p = 4.16x10-8); rs140005264, intron of ALDH16A1 (p = 7.34x10-8); and rs62220573, 19kb 3' of KRTAP21-3 (p = 9.52x10-8). The remaining significant donor SNPs were located in or near the following genes: EVX2, ATF7IP, MIR2054, TAS2R16, GPATCH1, RAB3GAP2, KIAA1328, FAM107B, ALDH16A1, TPP2, TXNDC5, ADAMTS19, HERPUD2 and 7 SNPs 3' of FGFR2. Conclusions: We identified several novel susceptibility loci associated with AR. UGT2B10 had the most variants associated with AR in this meta-analysis with p < 1x10-6. These SNPs need to be validated by independent cohorts and functionally assessed. United States National Institute for Allergy and Infectious Diseases grants: U01AI058013 and U19AI070119.